2013
DOI: 10.2217/rme.13.87
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Medicine and Hair Loss: How Hair Follicle Culture has Advanced our Understanding of Treatment Options for Androgenetic Alopecia

Abstract: Many of the current drug therapies for androgenetic alopecia were discovered serendipitously, with hair growth observed as an off-target effect when drugs were used to treat a different disorder. Subsequently, several studies using cultured cells have enabled identification of hair growth modulators with similar properties to the currently available drugs, which may also provide clinical benefit. In situations where the current therapeutics do not work, follicular unit transplantation is an alternative surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 97 publications
(73 reference statements)
0
25
0
Order By: Relevance
“…Cultured rat DPCs can self-aggregate to formed a papilla-like clump after subdermal injection, but spontaneous aggregation of cultured human DPCs injected into skin has not been observed 40, 41 . It has been shown that very rapid and extensive changes in molecular signature are associated with the transition of human DPCs from a three-dimensional to a two-dimensional environment, and that DPCs tend to lose their trichogenic ability when grown as traditional two-dimensional monolayers 42, 43 . Higgen et al .…”
Section: Discussionmentioning
confidence: 99%
“…Cultured rat DPCs can self-aggregate to formed a papilla-like clump after subdermal injection, but spontaneous aggregation of cultured human DPCs injected into skin has not been observed 40, 41 . It has been shown that very rapid and extensive changes in molecular signature are associated with the transition of human DPCs from a three-dimensional to a two-dimensional environment, and that DPCs tend to lose their trichogenic ability when grown as traditional two-dimensional monolayers 42, 43 . Higgen et al .…”
Section: Discussionmentioning
confidence: 99%
“…The compartmentalized expression of pro-and antiapoptotic factors in the HF is shown in Figure 3. A diverse array of additional molecules have been found to play a role in catagen induction, including FGF-5 [26,27], interferon (IFN)-g [28], substance P [29], and estrogens [30]. The apoptotic processes within the HF are also controlled by caspases 21, 23, 24, and 27 [21, 31, 32], and can also be triggered by the withdrawal of DP-derived growth factors or by apoptotic signals produced by mast cells located within the CTS [29,33,34].…”
Section: Catagenmentioning
confidence: 99%
“…The HF organ culture model is commonly used to determine whether small molecules or biologics may have a hair growth-promoting effect [69]. The advantage is that the effect of a compound can be assessed simultaneously on the epithelial and mesenchymal compartment of the HF.…”
Section: Androgenic Alopeciamentioning
confidence: 99%